PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP PENERIMAAN PERILAKU DISFUNGSI AUDIT PADA UNIT ORGANISASI TNI ANGKATAN LAUT - Sri Sukesi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
He purpose of this study is to determine the influence of Locus of Control, self-esteem relating to ambition, professional commitment, personal performance of employees to acceptance of dysfunctional audit behavior. The data of this research is officer of examiner who work in Ispektorat Jenderal TNI Navy force as many as 74 people. The research methodology used is descriptive statistic with validity test, reliability test and simple linear regression test. The results of this study indicate that the locus of control and professional commitment have a significant positive influence on the acceptance of dysfunctional audit behavior, while the self-esteem associated with ambition, personal performance and turn over interntion significantly negatively affect the acceptance of dysfunctional audit behavior. In order to control the reception of dysfunctional audit behavior, Irjenal needs to encourage self-esteem enhancement, improved personal performance of pegwai and turn over intention.Key Word : Locus of Control,Self Esteem In Relation to Ambition, Profesional commitment, profesional, self rate employee performance , turn over intension, Disfungsional Auditor Behaviour